Trans-escapho-perilunate fracture-dislocation. Case Presentation - Yaniel Truffin Rodriguez; Osmany Pérez martínez; Sergio Miguel Samón Matos; Horacio Samuel Suárez Monzón (Medisur)
Dislocations and perilunar fractures-dislocations are an infrequent entity (approximately 5% of post-traumatic injuries of the wrist).The most common event is that the distal row of the carpus is located dorsally with respect to the lunate. If there is an associated fracture, the most affected bone will be the scaphoid, at the height of the middle third and with a transverse line. These lesions often go unnoticed, hence the importance of studying them, reason for which it was decided to present the case of a 21-year-old patient, attended at the Hospital de Cienfuegos, for severe pain in the wrist after suffering a fall. The closed reduction of the dislocation was performed by the Tavernier maneuver and percutaneous fixation of the scaphoid fracture with two Kirschner wires. The scaphoid synthesis was maintained for eight weeks and the immobilization was withdrawn at 12 weeks after consolidation of the scaphoid fracture.